ANALYSIS OF THE USE OF SELECTED ENGINEERING SIMULATION TOOLS FOR MODELING DAYLIGHT - Piotrowska , Ewa (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
Improving the energy efficiency of buildings is dependent on a number of activities, especially taking into the issues of installation and equipment selection. One of the elements of the building is its lighting system, which should be considered, according to PN-EN 12464-1: 2012 as an electrical installation provided with mechanisms of control and taking into account the factor of daylight. The analysis of daylight is based on the use of specific standard models of sky that can perform daylighting and described in the report CIE.. With the development of the results, the type of software DIALux, Relux and Ecotect, analysis was carried out on the example of a public building for which the reference room determined intensity distribution of daylight and the total radiation power on the working surface. The simulation allow the orientation of the building in relation to the world, the size and position of windows and the effect of three common models of sky, including the luminance distribution of the celestial sphere. The results are presented in the form of distribution of monthly and hourly medium illuminance and uniformity of daylight on the working surface.